Effects of CaO, Al2O3 and MgO on liquidus temperatures of copper smelting and converting slags under controlled oxygen partial pressures - Zhao B.; Hayes P.; Jak E. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Phase equilibria of silicate slags relevant to the copper smelting/converting operations have been experimentally studied over a wide range of slag compositions, temperatures and atmospheric conditions. Selected systems are of industrial interest and fill the gaps in fundamental information required to systematically characterise and describe copper slag chemistry. The experimental procedures include equilibration of synthetic slag at high temperatures, rapid quenching of resulting phases, and accurate measurement of phase compositions using electron probe X-ray microanalysis (EPMA). The effects of CaO, Al2O3 and MgO on the phase equilibria of this slag system have been experimentally investigated in the temperature range 1200 to 1300 oC and oxygen partial pressures between 10-5 and 10-9 atm. It was found that spinel and silica are major primary phases in the composition range related to copper smelting/converting slags. In addition, olivine, diopside and pyroxene also appear at certain conditions. The presence of CaO, MgO and Al2O3 in the slag increases the spinel liquidus and decreases the silica liquidus. Liquidus temperatures in silica primary phase field are not sensitive to Po2; Liquidus temperatures in spinel primary phase field increase with increasing Po2. At 1300 oC and low Po2, the spinel (Fe2+,Mg2+)O.(Al3+,Fe3+) primary phase field can be replaced by wustite (Fe2+,Mg2+)O.